Problems of transforming labor legislation of Ukraine in connection with the dissemination of latest employment forms - Tetiana Vakhonieva, Mykola Inshyn,; Khrystyna Dzhura, Andrii Korotkikh, Anatolii Denysenko, (Opción)
The article explores the dynamic development of atypical forms of employment in the country and its impact on the Ukrainian labor market. The study highlights the need to create institutional and legal regulation of the latest forms of employment. This approach will facilitate the use of the positive aspects of atypical employment (adaptability, flexibility, the possibility of combining work and personal life, and others). The result of the reform of labor legislation in Ukraine should be the introduction of the latest forms of employment, establishing social dialogue, as well as increasing social guarantees for workers of atypical forms of employment to European labor standards.